Gender Discourse and Women Movements in Nahdlatul Ulama (NU) - RAHMAWATI, DIAN EKA (Jurnal Studi Pemerintahan, 2015)
The involvement of NU gender activists with the femi-nism ideas, the strengthening of democracy issues in Islam, and the effects of civil society development introduced by NGO or new social movement have made gender discourse and women movement in-side NU in dynamic. The occurrence of the new dis-courses brought by some NU gender activist results in the thought and movement among the NU activ-ists community. It also happens inside the NU’s struc-ture. Further implication, some activists who disagree with the thought and movement of Muslimat and Fatayat as NU female organization found other in-stitutions outside the NU’s structure. It shows that gender thought and women movement in NU is not static and anti-politics, on the contrary, it becomes dynamic and political because each actor involved inside try to affect and dominate each other both in discursive and praxis levels. This article aims to ex-plain critically the various studies that have been done about the gender discourse and the women movements in NU. The discussion will begin with the development of the gender discourse and women movements in the general overview, the develop-ment gender discourse and Muslim women move-ments, the influence of the gender discourse and women movements in NU. After that, it will be fol-lowed by the analysis of various literatures on gen-der discourse and women movements in NU as seen from the structural and cultural perspectives